Diversity of the Bacterial Microbiota of Anopheles Mosquitoes from Binh Phuoc Province, Vietnam - Ngo, Chung T.; Romano-Bertrand, Sara; Manguin, Sylvie; Jumas-Bilak, Estelle (Frontiers in Microbiology, 2016)
The naturally acquired microbiota of Anopheles can influence vector’s susceptibility to Plasmodium and its capacity to transmit them. Microbiota modification is a new challenge to limit disease transmission but it still needs advanced knowledges on bacterial community in Anopheles, especially in wild and infected specimens from diverse origin and species. Bacterial culture and 16S rRNA gene-PCR associated to Temporal Temperature Gradient Electrophoresis (TTGE) were applied to explore the bacterial diversity in the abdomen of 100 wild specimens (8 Anopheles species) collected in the Binh Phuoc Province, Vietnam. Culture and PCR-TTGE were complementary. The bacterial richness of the mosquito collection encompassed 105 genera belonging to 7 phyla, mostly Proteobacteria, Firmicutes and Actinobacteria. Staphylococcus, Clostridium and Bacillus in Firmicutes were the most prevalent genera. However, Proteobacteria represented by 57 genera was the most diversified phylum in Anopheles microbiota. The high overall of Anopheles-associated bacteria is confirmed with, to our knowledge, fifty-one genera described for the first time in Anopheles microbiota. However, the diversity per specimen was low with average diversity index (DI) and the average Shannon-Wiener score (H) of 4.843 and 5.569, respectively. The most represented bacterial genera were present in less than 30% of the specimens. Consequently, the core microbiota share by Anopheles from Binh Phuoc was very narrow, suggesting that Anopheles microbiota was greatly influenced by local environments. The repertory of bacterial genera in 2 specimens of An. dirus and An. pampanai naturally infected by Plasmodium vivax was also described as preliminary results. Finally, this study completed the repertory of bacteria associated to wild Anopheles. Anopheles associated-bacteria appeared specimen-dependant rather than mosquitoe species- or group-dependant. Their origin and the existence of Anopheles-specific bacterial taxa are discussed.